Australian Industrial and Construction Injuries, Diseases and Fatalities; and Recommendations for Safety Practices - Dejahang, Mehry (Curtin University, 2015)
The construction and building industry is one of the most dangerous industries worldwide. A review of the literature indicates a direct correlation between lack of safety culture and the occurrence of accidents within this industry. As a result of this research, nine OHS management system models have been recommended which are formed from a cluster of factors and from many different disciplines to be used as an assessment tool, to prevent accidents in construction or related industries.